The Prevalence and Morphology of Internal Jugular Venous Valves - Mohammad Afzal Khan; Faris Mohammad Nour Altaf; Mohammed Mazhar Hijazi; Ashraf Mohammmed Elsayed Ali Sakran (ziauddin University, 2024)
Background: Catheterization of the internal jugular vein (IJV) is common and used for several clinical procedures. Internal jugular venous valves are the only barrier between the heart and the brain. The presence and structure of these valves is variously described in the literature. The purpose of the current study was to explore the presence of IJV valves, their location and structure. Methods: Observations for the unilateral or bilateral presence or absence, exact location and number of cusps of the IJV valves were recorded by dissection on 62 formalin-fixed adult male and female cadavers. Results: IJV valves were found in 76.62% subjects. Most common of these valves were bicuspid (68.54%) while the least common were the tricuspid valves (0.80%). Unicuspid valves (collectively 7.25 %) were more common on the right side in the male while the same was true for the females on the left side. Only one tricuspid valve was observed on the right side in a female. Valves were mostly inferior to the clavicle (54.73 %) followed by posterior (38.94 %) while the least common position was superior (6.31 %).In the male the commonest location was inferior to the clavicle (70.00 %) followed by posterior (28.33%) while in the female the more common location was posterior (57.14%) followed by inferior (28.57%): the difference was significant. Superior position in the male was the least common (01.66%) while being relatively more common in the female (14.28%): the gender difference was statistically significant. Conclusion: The prevalence of internal jugular venous valves, their types and location are variable and probably reflect a genetic and racial attribute Key Words: Internal jugular vein, valves, morphology, anatomy, cannulation, catheterization